Tau profiling across Alzheimer's disease staging reveals vulnerability to disease pathophysiology. - Bezgin, Gleb; Pascoal, Tharick A.; Therriault, Joseph; Lussier, Firoza Z.; Servaes, Stijn; Kang, Min Su; Savard, Mélissa; Tissot, Cécile; Stevenson, Jenna; Wang, Yi-Ting; Ottoy, Julie; Rahmouni, Nesrine; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Background: Inter-individual variability in tau topography challenges the propagation hypothesis of tau aggregates. Methods: To address this gap, we propose the Manifold Component Analysis (MCA), for identifying pseudo-continuous profiles informed by the spatial continuity of stage regions. Results: Longitudinal and cross-sectional MCA in large aging cohort identified individual profiles (N = 753) expressing tau load in the entorhinal, limbic and neocortical regions. Using these profiles, we found neuropsychological and blood-based milestones of early and late disease stages. Finally, we also found evidence of rapid tau load increases and cognitive decline centered at the early-to-mid neocortical stages of Alzheimer's disease. Conclusions: Stage system based on tau load and spreading profiles across cortical areas provide a compelling framework for inferring pathophysiological prognosis in Alzheimer's disease.